A Feasibility Study on the Application of Basic Oxygen Furnace (BOF) Steel Slag for Railway Ballast Material - Koh, Taehoon; Moon, Sung-Woo; Jung, Hyuksang; Jeong, Yeonung (MDPI, 2018)
Railway ballast, for which natural crushed stone aggregates have been generally used, is an essential track component for the distribution of train loads along the rails and sleepers to the roadbed. However, the use of natural crushed stone aggregate causes environmental destruction as well as dust production in train service. This paper evaluates the feasibility of using the basic oxygen furnace (BOF) steel slag as railway ballast material. A series of physical and chemical quality tests are performed to investigate the characteristics of the materials associated with the effect of aging period due to the remaining free CaO and MgO in the BOF steel slag. Three different aging periods (i.e., 0, 3, and 6 months) are used to compare with various standards and the properties of the crushed stone aggregates. It is demonstrated that the physical and chemical properties of the BOF steel slag with different aging periods satisfy all requirements of standards sufficiently. Especially, the BOF steel slag without aging (i.e., 0 month) provides the similar physical and chemical properties, when compared to the BOF steel slag with aging (i.e., 3 and 6 months). Thus, it is possible to apply the BOF steel slag regardless of aging periods to the railway ballast materials instead of natural crushed stone aggregates.
Keywords: basic oxygen furnace (BOF) steel slag; electric arc furnace (EAF) steel slag; blast furnace (BF) iron slag; railway ballast; aging; free lime